2017
DOI: 10.11648/j.ejpm.20170504.12
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Knowledge and Attitude as Determinants of Oral Health Behavior in a Sample of Old People in Port Harcourt, Rivers State, Nigeria

Abstract: Adequate oral health knowledge, attitude and behavior are very important for the improvement of patient's oral health. The objective of the study was to assess the oral health knowledge, attitude and behavior of elderly people in Port Harcourt and determine the relationship between these variables. The research was descriptive survey and correlational in design. A total of 543 old people were selected by systematic random sampling. Data was collected with a self-developed Oral Health Assessment Questionnaire (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…In previous studies, correct oral health knowledge and proper oral health behaviors showed an effect on improving OHRQoL [20,21,45,46], which is in contrast to the results of this study; thus, further exploration is needed. However, a positive correlation was confirmed between oral health knowledge, oral health behavior, and OHRQoL, and these results are consistent with those of previous studies [47,48]. Oral health problems can be easily prevented through routine oral health management [17].…”
Section: Discussionsupporting
confidence: 91%
“…In previous studies, correct oral health knowledge and proper oral health behaviors showed an effect on improving OHRQoL [20,21,45,46], which is in contrast to the results of this study; thus, further exploration is needed. However, a positive correlation was confirmed between oral health knowledge, oral health behavior, and OHRQoL, and these results are consistent with those of previous studies [47,48]. Oral health problems can be easily prevented through routine oral health management [17].…”
Section: Discussionsupporting
confidence: 91%